Markers of stem cells in human ovarian granulosa cells: is there a clinical significance in ART? - Varras Michail; Griva Theodora; Kalles Vasileios; Akrivis Christodoulos; Paparisteidis Nikolaos (BMC, 2012)
Abstract Background The purpose of the study was to determine the incidence of gene expression of Oct-4 and DAZL, which are typical markers for stem cells, in human granulosa cells during ovarian stimulation in women with normal FSH levels undergoing IVF or ICSI and to discover any clinical significance of such expression in ART. Methods Twenty one women underwent ovulation induction for IVF or ICSI and ET with standard GnRH analogue-recombinant FSH protocol. Infertility causes were male and tubal factor. Cumulus-mature oocyte complexes were denuded separately and granulosa cells were analyzed for each patient separately using quantitative reverse-transcription-polymerase chain reaction analysis for Oct-4 and DAZL gene expression with G6PD gene as internal standard. Results G6PD and Oct-4 mRNA was detected in the granulosa cells in 47.6% (10/21). The median of Oct-4 mRNA/G6PD mRNA was 1.75 with intra-quarteral range from 0.10 to 98.21. The OCT-4 mRNA expression was statistically significantly correlated with the number of oocytes retrieved; when the Oct-4 mRNA expression was higher, then more than six oocytes were retrieved (p=0.037, Wilcoxon rank-sum). No detection of DAZL mRNA was found in granulosa cells. There was no additional statistically significant correlation between the levels of Oct-4 expression and FSH basal levels or estradiol peak levels or dosage of FSH for ovulation induction. No association was found between the presence or absence of Oct-4 mRNA expression in granulosa cells and ovarian response to gonadotropin stimulation. Also, no influence on pregnancy was observed between the presence or absence of Oct-4 mRNA expression in granulosa cells or to its expression levels accordingly. Conclusions Expression of OCT-4 mRNA, which is a typical stem cell marker and absence of expression of DAZL mRNA, which is a typical germ cell marker, suggest that a subpopulation of luteinized granulosa cells in healthy ovarian follicles (47.6%) consists of stem cells, which are not originated from primordial germ cells. Absence of Oct-4 gene expression in more than half of the cases means probably the end of the productive journey of these cells, towards the oocyte.